Qualitative Phytochemical Analysis and Antibacterial Potential of Chromolena Odorata Leaves as affected by Soxhlet and Maceration Extraction - Mohd Fauzi, Noor Akhmazillah; Mohd Shamsuddin Tan, Nur Farahida (Journal of Advanced Industrial Technology and Application, 2020)
Chromolaena odorata is locally known as â€œPokok Kapal Terbangâ€. This species is a perennial weed of plantation crops and cleared lands and it comes from the family of Asteraceae (Compositae) and can be found abundantly in Malaysia. The fresh leaves and extract of this plant commonly related to herbal treatment in some developing countries for burns, soft tissue wounds, and skin infections. However, it has not been thoroughly investigated and their phytochemical and cytotoxicity potential virtually unknown. The objective of this study is to investigate the antibacterial potential of C. odorata leaves extract and its phytochemicals content. The Soxhlet and maceration method of extraction were carried out and then were tested for its phytochemicals content namely saponins, terpenoids, tannin and flavonoids. The antibacterial activity of extracted samples was tested against gram-positive Staphylococcus epidermidis and gram-negative Escherichia coli by using disc diffusion method. The results showed that the percentage yield of leaves extract using Soxhlet method for 12 hours was 21.60 %, which is higher than maceration method (with 18.10% of yield for 120 hours extraction). Qualitative phytochemicals analyses revealed that both Soxhlet and maceration- extracted of C. odorata leaves contain tannins, flavonoids, saponins and terpenoids. All the extract showed a good antibacterial properties against both S. epidermidis and E.coli strain with inhibition zone ranging from 8.33 mm to 11.00 mm and 6.00 mm-10.50 mm, respectively. The extract was then further applied onto a cream and the anti-bacterial activity against S.epidermidis was recorded in which the largest inhibition zone of 9.50 mm was obtained. Whereas anti-bacterial activity against E. coli was found only in Soxhlet extracted sample (12 hours treatment time) with 12.00 mm diameter of inhibition zone. This study showed  that C. odorata leaves extract has a great potential to be developed as antibacterial agent which can be incorporated with a cream for medical and pharmaceutical use.